MEMBANGUN BENTENG IMAN MELALUI PERAN KELUAGA KRISTEN DALAM MEMBENTUK KARAKTER ROHANI ANAK DI TENGAH GEMPURAN ERA DIGITAL - ADINCE TOTO; AGNESTIA FEO; DIANA SOLE; VEBIANA I. OTEMUSU; NIKSON BETTY (JUTEQ: JURNAL TEOLOGI & TAFSIR, 2026)
The presence of digital technology has fundamentally transformed the face of Christian family life, creating new challenges while opening opportunities in the implementation of Christian Religious Education within the household environment. This study examines how Christian families can carry out their educational function in shaping children's spiritual character amid the continuous development of the digital technology wave. Through a descriptive qualitative approach, this study finds that Christian families are in a challenging situation between utilizing technological advances and maintaining biblical faith values. The research results indicate that parents require a comprehensive approach that combines intensive accompaniment, understanding of digital technology based on Christian values, and the utilization of technology as a means of teaching faith. Thus, the main findings show that family spiritual resilience greatly depends on parents' ability to create a healthy digital environment, where technology does not replace but rather enriches spiritual communication within the family. This research recommends a comprehensive approach that integrates theological principles with wisdom in using digital technology, so that Christian families can become a strong fortress of faith for generations born and raised in the digital era.